New perspectives on Microsoft Access 97 comprehensive - Adamski, Joseph J. 1945-; Hommel, Charles; Finnegan, Kathleen T. (New perspectives series, 1998)
This volume explores new perspectives in Microsoft Access 97. Tutorials cover querying a database, creating reports and forms, and integrating Access with other applications.